1994
DOI: 10.1128/aac.38.3.563
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy of drug-resistant Trypanosoma brucei rhodesiense infections in mice using DL-alpha-difluoromethylornithine and standard trypanocides

Abstract: Combinations of DL-ot-difluoromethylornithine (DFMO; eflornithine; Ornidyl) with either suramin or melarsen oxide were found to be effective against acute laboratory model infections with Trypanosoma brucei rhodesiense. We used clinical isolates known to be resistant to these drugs when used singly. An infection with a melarsen oxide-refractory isolate was cured by a combination of low-dose DFMO (0.5% in the drinking water) plus low-dose suramin (1 mg/kg of body weight given intraperitoneally). Another strain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 20 publications
(27 reference statements)
1
32
0
Order By: Relevance
“…Evaluation of AN3520 and SCYX6759 against stage 2 CNS infections was conducted with a chronic diseaseinducing strain (TREU 667) of T. b. brucei (3,4,5). Female Swiss Webster mice were infected intraperitoneally with 1 ϫ 10 4 parasites (200 l) followed by treatment with a single 10 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of AN3520 and SCYX6759 against stage 2 CNS infections was conducted with a chronic diseaseinducing strain (TREU 667) of T. b. brucei (3,4,5). Female Swiss Webster mice were infected intraperitoneally with 1 ϫ 10 4 parasites (200 l) followed by treatment with a single 10 mg/kg i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were immediately removed from the cages and euthanized upon recrudescence. Animals remaining aparasitemic for at least 180 days after the end of the treatment period were considered cured (3,4,5). Brain homogenates or the blood of oxaborole-cured animals failed to generate infection when injected into naive, cyclophosphamide-immunosuppressed mice.…”
Section: Methodsmentioning
confidence: 99%
“…If suramin does use this type of pathway to cross the brain barriers, different regional expression of the receptors may explain the ability of suramin to reach select areas of the CNS. Furthermore, coadministration of suramin with drugs that are active against the second, CNS stage, namely, melarsoprol, nifurtimox, and eflornithine, has been shown to improve cure rates (2,7,9,19,34). Inhibition by suramin of the P-glycoprotein (P-gp) transporter at the BBB, thus preventing the removal of the second-stage drug from the brain, has been put forward as a possible explanation for this observation (12,13), but this hypothesis remains untested.…”
Section: H]suramin Would Be Unlikely To Treat the Second Or Cns Stagementioning
confidence: 99%
“…rhodesiense and T.b. brucei infections (Clarkson et al, 1984;Bacchi et al, 1987Bacchi et al, ,1994. We have also revealed that pentamidine (another first-stage drug) can cross the BBB, but is removed by ATP binding cassette transporters including P-glycoprotein (P-gp) and MRP (Sanderson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%